2021
DOI: 10.3390/cells10112925
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Interactions of RUNX with the Hippo–YAP Pathway

Abstract: The Hippo–YAP signaling pathway serves roles in cell proliferation, stem cell renewal/maintenance, differentiation and apoptosis. Many of its functions are central to early development, adult tissue repair/regeneration and not surprisingly, tumorigenesis and metastasis. The Hippo pathway represses the activity of YAP and paralog TAZ by modulating cell proliferation and promoting differentiation to maintain tissue homeostasis and proper organ size. Similarly, master regulators of development RUNX transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…Of these six genes, we identified Runx1 as an interesting candidate as it has been used as a marker of cardiomyocyte regression to a less differentiated state prior to cell cycle re-entry (D’Uva et al, 2015; Kubin et al, 2011). In addition, Runx1 has been shown to interact with Yap (Chuang and Ito, 2021), a transcription factor well established for its regulation of cardiomyocyte proliferation (Monroe et al, 2019). With this in mind, we first asked if Runx1-positive cardiomyocytes were more prevalent in A/J versus C57Bl/6J hearts at P21, just preceding expansion of the MNDCM population in A/Js.…”
Section: Resultsmentioning
confidence: 99%
“…Of these six genes, we identified Runx1 as an interesting candidate as it has been used as a marker of cardiomyocyte regression to a less differentiated state prior to cell cycle re-entry (D’Uva et al, 2015; Kubin et al, 2011). In addition, Runx1 has been shown to interact with Yap (Chuang and Ito, 2021), a transcription factor well established for its regulation of cardiomyocyte proliferation (Monroe et al, 2019). With this in mind, we first asked if Runx1-positive cardiomyocytes were more prevalent in A/J versus C57Bl/6J hearts at P21, just preceding expansion of the MNDCM population in A/Js.…”
Section: Resultsmentioning
confidence: 99%
“…Although falling outside of the scope of this review, Runx has been widely demonstrated to be related to tumor development, cancer progression, and metastasis in different organs [ 26 , 27 ].…”
Section: Runx and Energy Statementioning
confidence: 99%
“…Activated LATS1/2 and MOB1 in turn together phosphorylate the main effectors of the Hippo pathway, YAP and transcriptional coactivator PDZ-binding motif (TAZ), leading to their cytoplasmic sequestration and degradation (13,14). When Hippo signaling is inactivated, unphosphorylated YAP and TAZ translocate into the nucleus and interact with transcriptional factors, such as TEA-domain family members (TEADs), mothers against DPP homolog (SMADs), runt related transcription factor (RUNX) and zinc finger E-box binding homeobox 1 (ZEB1), thereby regulating genes involved in cell survival, migration and metabolism (15)(16)(17)(18). Not surprisingly, substantial evidence has shown that dysregulation of the Hippo pathway is involved in various human cancers.…”
Section: Introductionmentioning
confidence: 99%